Pengaruh Rasio Likuiditas Dan Rasio Solvabilitas Terhadap Rasio Profitabilitas Di PT Indofood Sukses Makmur Tbk Periode 2011-2021 - Untung Eko Setyasari (LPPM POLITEKNIK LP3I BANDUNG, 2022)
Financial ratio analysis is a common method used to measure the strengths or weaknesses faced by companies in the financial sector. The purpose of this study are: 1) To find out how the liquidity ratio (Current Ratio), solvency ratio (Debt to Assets Ratio) and profitability ratio (Return On Assets) in PT Indofood CBP Sukses Makmur Tbk. 2) To find out how the liquidity ratio (Current Ratio) to profitability ratio (Return on Assets) 3) To find out how the solvency ratio (Debt to Assets Ratio) to profitability ratio (Return on Assets). 4) To find out how the liquidity ratio (Current Ratio) and solvency ratio (Debt to Assets Ratio) together influence the profitability ratio (Return on Assets. The research method used in this research is descriptive and verification methods. Data collection techniques are carried out through field research and literature studies. Data analysis techniques were carried out through verification verification with multiple linear regression testing. The significance value for the liquidity ratio is 0.186 while for the solvability ratio 0.07 so that partially the liquidity do not affect the profitability ratio, while solvency ratio have affect to profitabilty ratio. The F test also shows a significance value of 0.057 and> 0.05 so that silmatic ratio of liquidity and solvency does not affect profitability ratios.